Tough on crime: the rise of punitive populism in Latin America - Bonner, Michelle D. (Pitt Latin American series, 2019)
Introduction. Media and the rise of punitive populism -- Interpreting statistics on crime, insecurity, and police violence -- The mass media's role in emotions and public opinion -- Comparing media systems : Argentina and Chile -- Journalists' preference for tough-on-crime sources -- The rise of punitive voices from within the state -- The rise of punitive voices from civil society.